Integrasi Esg dan Good Corporate Governance Sebagai Strategi Mewujudkan Tujuan Pembangunan Berkelanjutan (SDGs) - Adji Darmawan; Mila Oktaviani; Helmi Veronica Pasaribu; Irwan Agustuslan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the strategic integration of Environmental, Social, and Governance (ESG) and Good Corporate Governance (GCG) as a means to support the achievement of the Sustainable Development Goals (SDGs). Using a qualitative descriptive method through content analysis of secondary data, the research analyzes the relevance of ESG and GCG in corporate strategy. The findings show that ESG provides a framework for identifying sustainability-related risks and opportunities, while GCG ensures ethical, transparent, and accountable governance. Companies integrating these two pillars demonstrate better performance in sustainability, increased competitiveness, and greater investor trust. Case studies from Indonesian companies such as PT SUCOFINDO and PT Len Industri illustrate successful ESG-GCG implementation that aligns with various SDG targets. Nonetheless, challenges remain, including resource constraints and limited managerial awareness. The study concludes that the synergy between ESG and GCG is essential in building resilient and sustainable businesses. Further research is recommended to develop implementation models across industries and support policy improvements in ESG governance.